Struktur Komunitas Fitoplankton di Kolam Bekas Pertambangan Batubara Desa Kampung Baru Kecamatan Cempaka - Sukoco Sukoco; Gunawan Gunawan; Muhamat Muhamat (Universitas Lambung Mangkurat, 2020)
This study aims to determine the structure of phytoplankton communities in the pool are former coal mining Desa Kampung Baru Kecamatan Cempaka which include abundance, diversity, uniformity and dominance. Phytoplankton samples taken in two pools with a purposive sampling method with a three-point shooting at each pond. Sampling was performed three times. Phylum of phytoplankton were identified in both pools as much as 2 phylum (Chloropyta and Chrysopita) with 17 genera. Average abundance of phytoplankton in the first pool of 7174 ind / liter and 6873 ind / liter in the second pool. The average diversity index of phytoplankton in the first pool of 1.540 and 1.621 in the second pool. Average uniformity index of phytoplankton in the first pool of 0622 and 0.623 in the second pool. The average index of phytoplankton dominance in the first pool of 0271 and 0250 in the second pool. Analysis of community structure (abundance, diversity, uniformity and dominance) shows the condition of the two ponds in the state is quite stable and capable of supporting life inside the phytoplankton. Where the pool in the fertility rate is the level of contamination is, the conditions included in the category of individuals spread more evenly and there are no species that dominate other species in the extreme.